On the correct authorship, spelling, and type species of genus Dasongius (Pauropoda: Pauropodidae) - Martínez-Muñoz, Carlos A.; Bu, Yun (Zootaxa, 2021)
The genus Songius Sun & Guo in Guo et al., 2010 (Pauropoda: Pauropodidae) was established for two new species from China: Songius rugosus Sun & Guo in Guo et al., 2010 and Songius bicruris Guo & Sun in Guo et al., 2010. The manuscript was received by the journal Zoological Science on 7th April 2010 and the article is displayed on the BioOne platform with the publication date of 1st November 2010. In the same year, Yin et al. (2010) established the genus Songius Yin & Li in Yin et al., 2010 (Coleoptera: Staphylinidae: Pselaphinae).